موقف فخر الدين الرازي من الحروف الزائد فى القرآن الكريم: لام الصلة في مفاتيح الغيب نموذجاً - إبراهيمي، طاهر (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست - معهد الآداب واللغات, 2019)
نعالج في هذا البحث إشكالا علميا يتمثل في الحكم على بعض كلمات الوحي بالزيادة، هذا الإشكال الذي نشأ نتيجة تباين مناهج الدرس عند علماء الإسلام، إلا أنه برز بشدة في ميدان التفسير لأنه مصب للعلوم اللغوية والشرعية من جهة، ولأن قداسة النص القرآني تفرض على المفسر الحذر الاصطلاحي والمفهومي من جهة أخرى. وانطلاقا من هذا المعطى عرضنا لمفهوم مصطلح الزيادة والخلاف في وقوعه والكلمات التي حكم عليها بالزيادة، ثم عرجنا على حرف (لا) ببيان خصوصيته وسبب اختياره، ثم ذكرنا توجيهات فخر الدين الرازي لحرف (لا) في جل مواضعه بعد تحقيق مصطلح الحرف الزائد عنده، وبيان موقفه من القائلين بالزيادة في القرآن الكريم.
We deal in this study with a scientific issue which consists in considering some words of the Quran as extra. This issue is due to the contrast in teaching methodologies adopted by Islamic scholars. Though, it is more obvious in the field of exegesis, as it is, on the one hand, the repository of linguistic and religious sciences, on the other hand, the holiness of the Quranic texts imposes on the exegete terminological and conceptual caution. On this basis, we have dealt broadly with the term ‘addition’ and the divergence as to its occurrence and the words that are deemed as additional, then we have focused on the particle «Lâ» by showing its particularities and why we have chosen to study it. Then, we have mentioned the directions of Fakhr Ad-Dîn Ar-Râzi about the particle «Lâ» where it occurred after ascertaining the meaning of the term ‘additional particle’ to him and have shown his position towards those who argue in favor of the view that there may be additional terms in the Holy Quran.
Keywords: القرآن الكريم -- الرازي، فخر الدين -- العلوم الشرعية